1987
DOI: 10.1017/s0043174500079133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pine Kraft Lignins for Controlled Release of Alachlor and Metribuzin

Abstract: The controlled release of metribuzin [4-amino-6-(1,1-dimethylethyl)-3-(methylthio)-1,2,4-triazin-5(4H)-one] and alachlor [2-chloro-N-(2,6-diethylphenyl)-N-(methoxymethyl)acetamide] from pine kraft lignin was studied using14C-labeled herbicides and3H-labeled lignin with soil thin-layer chromatography. NB-5203-58 series and PC940 series kraft lignins adsorbed and desorbed metribuzin as soil plates were developed with water. PC671, a formulated kraft lignin control release product, did not provide controlled rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…The lignins proved to be good sorbents of the pesticides studied. The higher sorption observed for L2, with an intermediate molecular weight with respect to L1 and L3, is in contrast with the findings of Riggle and Penner (1987), who reported a positive relationship between the sorption of metribuzin by different commercial alkali lignins and the molecular size of those lignins. The sorption capacity of HA was greater than that of lignins for linuron and alachlor.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The lignins proved to be good sorbents of the pesticides studied. The higher sorption observed for L2, with an intermediate molecular weight with respect to L1 and L3, is in contrast with the findings of Riggle and Penner (1987), who reported a positive relationship between the sorption of metribuzin by different commercial alkali lignins and the molecular size of those lignins. The sorption capacity of HA was greater than that of lignins for linuron and alachlor.…”
Section: Resultscontrasting
confidence: 99%
“…However, studies on pesticides, compounds with large complex structures with different functional groups able to interact with such organic components, are less common. In general, the aim of the studies performed has been to determine the behavior of lignins as pesticide support in controlled‐release formulations (Riggle and Penner, 1987, 1988; Ferraz et al, 1997) or to evaluate their influence as a precursor of the soil organic matter (OM) in the determination of pesticide behavior in soils (Benoit et al, 1999; Beulke et al, 2005). The mechanism of action governing the retention of pesticide by these materials has been scarcely addressed (Torrents et al, 1997).…”
mentioning
confidence: 99%
“…The formation of covalent bonds is also possible. In fact, it has been reported that some products from the enzymatic transformation of pesticides may polymerize into humus macromolecules (Riggle et al 1987;Bartha, 1980;Wershaw, 1989;Haider et al, 1988 (Martínez-Iñigo, 1991). In the present study, the humified biomass from this plant-starting material is applied to soils with a negligible humus content to prove the effect of organic matter on pesticide fixation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled-release herbicide formulations have been investigated for several years. Methods studied include, but are not limited to, pine kraft lignin (10,11), cellulose acetate cloth (3), organic mulches (7), cross-linked corn starches (8), starch xanthate (1,9,13,17), gum xanthan (2), plaster of paris tablets (5,6,15), and dicalcium phosphate tablets (12,16).…”
Section: Introductionmentioning
confidence: 99%